Negotiating National Equality in the Austrian Silesian Diet 1905-1914 - Paula Krajnik (Central Europe)
At the turn of the twentieth century, nationalized conflicts affected all levels of politics in the Habsburg monarchy. Since the 1890s, Polish and Czech members of the Austrian Silesian provincial diet demanded equality with Austria’s German-speaking citizens, granting them the Basic Law as two of the crownlands’ recognized nationalities. With the Moravian Compromise of 1905, which attempted to solve the national conflict between Czechs and Germans and ensured national equality on a provincial level, Czechs and Poles of Silesia called for electoral and language law reforms of a similar model. Despite many years of attempts, the Silesian diet found no national compromise. This article will provide an overview of the struggle for national equality and attempts at a national compromise in Silesia from the Moravian Compromise in 1905 until the closure of the provincial diet in 1914. By analyzing the stenographic minutes of the Silesian provincial diet, this article traces the attempts at national equalization and pacification, how members of the provincial parliament debated national equalization and pacification, and aims to identify the reasons for their failure of these attempts. Reforms of the administrative language laws and school politics to resolve national conflicts never concretized, although national conflicts heavily characterized these topics. The Viennese central government rejected two electoral reform drafts for their lack of measures to solve the national conflicts; further drafts never materialized. A Silesian Compromise never became realized in part due to the unwillingness and lack of interest to find a compromise on the side of the diet’s German majority, which was easily able to outvote its Slavic minority and refused many of their demands out of fear of losing their hegemony.